Tinjauan Etis terhadap Rekayasa Genetika dalam Kajian Human Cloning - Darwin Sibarani (Publisher STPKat, 2024)
Biotechnology has brought extraordinary advances in health, agriculture, and scientific research, but it has also raised complex ethical challenges, especially in human cloning technology. In the context of biotechnology, cloning refers to the creation of a genetic copy of an organism, and although animal cloning has been successfully carried out for research purposes and increasing agricultural yields, human cloning remains a controversial issue. Ethically, human cloning raises a number of questions regarding human rights, identity, and the potential misuse of this technology for unethical purposes, such as genetic programming or the creation of